The Gestational Age, Exclusive Breastfeeding, Attitude Complementary Foods Associated with Stunting Infants - Atik Pramesti Wilujeng Atik (Alta Dharma Publisher, 2021)
Introduction : Many factors influence the occurrence of stunting in toddlers, but the most important factor influencing the incidence of stunting comes from the mother. Objective: This study aims to analyze the relationship between gestational age of infants, exclusive breastfeeding and mother's attitude in giving complementary foods with the incidence of stunting in infants aged 6-24 months. Method: The research design is Cross Sectional. The sampling technique used was purposive sampling involving 125 mothers of infants aged 6-24 months. Result: The results found that gestational age (p value = 0.016), exclusive breastfeeding (p value = 0.027) and complementary feeding (p value = 0.00) have positive correlation with attitude and complementary feeding. The babies born with a small gestational age are at risk of stunting. Exclusive breastfeeding for infants aged 0-6 months followed by a positive mother's attitude in preparing and providing quality complementary foods can reduce the risk of babies experiencing stunting, so nurses' efforts are needed to provide health education to mothers to optimize their role in infant care and nutrition. Recommendation: Health workers, both nurses and midwives, should increase their role in providing health education to mothers with babies aged 6-24 months about the importance of Antenatal Care, health education about the benefits of breastfeeding and forming of breastfeeding motivators and providing health education to mothers under five how to arrange a supplementary food menu for toddlers